2008
DOI: 10.3177/jnsv.54.266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corosolic Acid on the Hydrolysis of Disaccharides

Abstract: SummaryThe banaba leaf ( Lagerstroemia speciosa L.) has been used in traditional Oriental medicine to treat diabetes in the Philippines. It contains corosolic acid (CA), a compound which has a hypoglycemic effect. We examined the effect of CA on blood glucose levels and the hydrolysis of disaccharides in the small intestine in mice. CA (10 mg/kg body weight) improved hyperglycemia after an oral administration of sucrose, and significantly reduced the hydrolysis of sucrose in the small intestine. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
6
0
2
Order By: Relevance
“…In this study, a sugar solution was administered 30 min orally after the corosolic acid, and blood samples were drawn at 30, 60, and 120 min [38]. These results agree with the observations of Suzuki et al who showed that an extract of Banaba leaves inhibited sucrase activity and exerted hypoglycemic effects through multiple mechanisms [27].…”
Section: Animal Studiessupporting
confidence: 86%
“…In this study, a sugar solution was administered 30 min orally after the corosolic acid, and blood samples were drawn at 30, 60, and 120 min [38]. These results agree with the observations of Suzuki et al who showed that an extract of Banaba leaves inhibited sucrase activity and exerted hypoglycemic effects through multiple mechanisms [27].…”
Section: Animal Studiessupporting
confidence: 86%
“…In a study in mice, Takagi et al () demonstrated that an oral dose of 10 mg/kg corosolic acid suspended in water inhibited the intestinal hydrolysis of sucrose but not maltose or lactose, thereby at least in part facilitating the lowering of blood glucose levels since sucrose is a disaccharide composed of glucose plus fructose. In this study, a sugar solution was administered 30 min orally after the corosolic acid, and blood samples were drawn at 30, 60 and 120 min.…”
Section: Animal Studiesmentioning
confidence: 99%
“…This acid is one of the active constituents of Lagerstroemia speciosa L., banaba leaf. The plant is used traditionally in Philippines to treat diabetes and was studied by Takagi et al [89] who referred the antidiabetic effect to the inhibition of sucrose hydrolysis. However, the effect of corosolic acid on GLUT-4 can not be ruled out, although this requires further verification In another study [90] , the 3T3-L1 adipocytes were used to prove that the methanolic extract of Liriope platyphylla Wang et Tang ( LPWT), Liliaceae, increased insulin-induced glucose uptake in adipocytes, by virtue of its homoisoflavone.…”
Section: Enhancement Of Glucose Uptake and Upregulation Of Glucose Trmentioning
confidence: 99%